Pengaruh Keselamatan dan Kesehatan Kerja (K3) Dan Disiplin Kerja Terhadap Produktivitas Kerja Pada Karyawan Bagian ProduksiPT. Pura Barutama Unit Paper Mill Kudus - Osha Silvia Anggreini; Hari Susanta Nugraha; Reni Shinta Dewi (Universitas Diponegoro, 2014)
This research was motivated by the importance of human resources in an enterprise to produce quality products in the middle of business competition in the globalization era. Human resources is a key factor in mobilizing other resources within the company. PT. Pura Barutama is a manufacturing company which is engaged in the printing industry, the largest in Southeast Asia, which produces various types of paper. But if seen growth results production at PT. Pura Barutama Units Paper Mill was still not stable each year, in which experiencing in 2013 decreased production significantly compared to the previous year. The purpose of this research is to know the level of productivity of work in the production section of the PT. Pura Barutama Unit Paper Mill. This research’s type is eksplanatory, techniques of data collection using questionnaires, interviews and studies library. Sampling techniques using cluster random sampling. The sample in this research totalled 81 respondents who were employees of the production section of PT. Pura Barutama Unit Paper Mill. Methods of analysis used in this study is the analysis of simple and multiple regression, with validity tests and reliability tests. Result the research indicated that k3 and discipline work as partialy and simultaneously affect productivity work. Based on these results, PT. Pura Barutama Unit Paper Mill must be able to maintain and increase productivity work employees by giving good k3 to employees and maintain discipline of employees.